2012
DOI: 10.1038/ncomms2147
|View full text |Cite
|
Sign up to set email alerts
|

The convergent evolution of defensive polyacetylenic fatty acid biosynthesis genes in soldier beetles

Abstract: The defensive and bioactive polyacetylenic fatty acid, 8Z-dihydromatricaria acid, is sequestered within a wide range of organisms, including plants, fungi and soldier beetles. The 8Z-dihydromatricaria acid is concentrated in the defence and accessory glands of soldier beetles to repel avian predators and protect eggs. In eukaryotes, acetylenic modifications of fatty acids are catalysed by acetylenases, which are desaturase-like enzymes that act on existing double bonds. Here we obtained acyl Coenzyme A-linked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Such enzymes are often implicated in the polyyne biosynthesis. For example, in soldier beetles, monounsaturated oleic acid is converted in five steps by three desaturases into the immediate precursor of the polyacetylenic compound dihydromatricaria acid (Haritos et al, 2012). One of the genes in cluster K (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Such enzymes are often implicated in the polyyne biosynthesis. For example, in soldier beetles, monounsaturated oleic acid is converted in five steps by three desaturases into the immediate precursor of the polyacetylenic compound dihydromatricaria acid (Haritos et al, 2012). One of the genes in cluster K (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Bifunctional FAD2 Δ12 and Δ14 desaturases are not the only enzymes that can catalyze fatty acid desaturation in two positions, as an enzyme from the soldier beetle Chauliognathus lugubris catalyzes both Δ14 crepenynate desaturation and Δ16 desaturation of 9Zoctadecen-12,14-diynoic acid (Haritos et al, 2012). This insect desaturase is another example of an enzyme that can catalyze desaturation in one position and then, after that same position has been acetylenated, can catalyze another desaturation two carbons further down the chain from the initial reaction site.…”
Section: Specificity and Structural Features Of Carrot Fad2 Desaturasmentioning
confidence: 99%
“…Hence, C18:2 Δ9,12 was considered to be an essential nutrient for animals (Cripps et al, 1986;Malcicka et al, 2018). However, studies on insects (Blaul et al, 2014;Blomquist et al, 1982;Buckner and Hagen, 2003;Cripps et al, 1986Cripps et al, , 1990Haritos et al, 2012;Malcicka et al, 2018;Zhou et al, 2008), springtails (Malcicka et al, 2017), nematodes (Peyou-Ndi et al, 2000), gastropods (Weinert et al, 1993), mites (Aboshi et al, 2013;Shimizu et al, 2014) and a variety of aquatic invertebrates (Kabeya et al, 2018) have shown that not all animals depend on dietary uptake of C18:2 Δ9,12 but are able to synthesise it de novo. Evidence for the presence of Δ12-FADs in insects is mostly based on stable and radioactive isotope labelling experiments (Blaul et al, 2014;Blomquist et al, 1982;Buckner and Hagen, 2003;Cripps et al, 1986;Malcicka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This approach, however, does not completely rule out the possibility that C18:2 Δ9,12 is produced by associated microorganisms rather than by the studied animal itself. Unequivocal evidence for C18:2 Δ9,12 biosynthetic capacity requires isolation and functional characterisation of insect-derived Δ12-FAD genes, which has been achieved so far only for the house cricket Acheta domesticus (AdD12Des, here referred to as Adom_D12) (Zhou et al, 2008), the soldier beetle Chauliognathus lugubris (CL10, Clug_D12) (Haritos et al, 2012) and the red flour beetle Tribolium castaneum (TcD12Des, Tcas_D12) (Haritos et al, 2014;Zhou et al, 2008). It is unknown, however, whether the Δ12-FADs in these species are involved in primary fatty acid metabolism or pheromone biosynthesis.…”
Section: Introductionmentioning
confidence: 99%